Measurement of high-Q(2) charged current cross sections in e(-)p deep inelastic scattering at HERA - Chekanov, S; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; Bellagamba, L; Boscherini, D; et al. (2002)
Cross sections for e - p charged current deep inelastic scattering have been measured at a centre-of-mass energy of 318 GeV with an integrated luminosity of 16.4 pb -1 using the ZEUS detector at HERA. Differential cross sections dσ/dQ 2, dσ/dx and dσ/dy are presented for Q 2 > 200 GeV 2. In addition, d 2σ/(dxdQ 2) was measured in the kinematic range 280 GeV 2 < Q 2 < 30 000 GeV 2 and 0.015 < × < 0.42. The predictions of the Standard Model agree well with the measured cross sections. The mass of the W boson, determined from a fit to dσ/dQ 2, is M W = 80.3±2.1(stat.) ± 1.2(syst.) ± 1.0(PDF) GeV. © 2002 Published by Elsevier Science B.V.